Graph approximations of set-valued maps under constraints - Mederski, Jarosław (Topological Methods in Nonlinear Analysis, 2012)
In the paper we study the existence of constrained graph approximations of set-valued maps with non-convex values. We prove, in particular, that any open neighbourhood of the graph of a map satisfying the so-called topological tangency assumptions contains a graph of constrained continuous single-valued map provided that the domain is finite-dimensional.